2015
DOI: 10.1186/s40497-015-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Identification the main challenges of small and medium sized enterprises in exploiting of innovative opportunities (Case study: Iran SMEs)

Abstract: Erratum After publication, it was highlighted that the manuscript: 'Identification the main challenges of small and medium sized enterprises in exploiting of innovative opportunities (Case study: Iran SMEs)' (Farsi and Toghraee 2014) contained a typing error in the title. The correct title is: 'Identification of the main challenges of small and medium sized enterprises in exploiting innovative opportunities (Case study: Iran SMEs)'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…H8 = Inadequate entrepreneurial characteristics will relate negatively to SMEs WTI Technological capacities: Past research reports had revealed that majority of SMEs have not subscribed to the emerging technological trend hence many of them are lagging behind their large firm counterparts (Soon 2006;Asare, 2014;Ocloo et al, 2014;Farsi & Togharee, 2014;Bouazza et al, 2015). Farsi & Toghraee (2014) found that even the little advanced business entrepreneurs are frequently live in limbo of these new technologies and even if they aware of them, it inapplicable in the local context or not affordable as well as in disharmony with the indigenous situations. Moreover, the study found that foreign companies are still the frontiers in terms of implementing new technologies.…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…H8 = Inadequate entrepreneurial characteristics will relate negatively to SMEs WTI Technological capacities: Past research reports had revealed that majority of SMEs have not subscribed to the emerging technological trend hence many of them are lagging behind their large firm counterparts (Soon 2006;Asare, 2014;Ocloo et al, 2014;Farsi & Togharee, 2014;Bouazza et al, 2015). Farsi & Toghraee (2014) found that even the little advanced business entrepreneurs are frequently live in limbo of these new technologies and even if they aware of them, it inapplicable in the local context or not affordable as well as in disharmony with the indigenous situations. Moreover, the study found that foreign companies are still the frontiers in terms of implementing new technologies.…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
“…These challenges stretch across the entire value chain of the SMEs operational areas. These constraints include; finance/credit access (Ayyagari et al, 2011;Khaled, 2012;WBG, 2015;Quartey et al, 2017;Appiah, et al 2018), competition, (Bouazza et al, 2015;Quartey et al, 2017;Appiah, et al 2018), entrepreneurial capabilities (Kazimoto, 2014;Abood et al, 2014, Bouazza et al, 2015 human resource capabilities (Farsi & Toghraee, 2014;Bouazza et al, 2015), technological capabilities (Bouazza et al, 2015Farsi & Toghraee, 2014, managerial capabilities (Bouazza et al, 2015;Quartey et al, 2017) corruption among regulators (Abood et al, 2014;Bouazza et al, 2015), inadequate information access (Farsi & Toghraee, 2014;Appiah), inadequate institutional support (Bouazza et al, 2015;Appiah et al, 2018). In a recent study Appiah etal.…”
Section: Introductionmentioning
confidence: 99%
“…The Farsi et al (2014) study result showed that SMEs in Iran faced some challenges as it suits the six main challenges. The two biggest challenges of SMEs for exploiting innovative opportunities are technological change and inadequate education and skills.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to Farsi et al (2014), there are six main challenges as follows: (1) Lack of managerial training and experience that consists of management style, poor managerial ability, and lack of educational background; (2) Inadequate education and skills that consists of not quite well equipped in education and skills, lack of college level education; (3) National policy and regulatory environment that consists of unpredictable government policies and grand corruption; (4) Technological change consists of unfamiliarity with new technologies and either not locally available or not affordable or not situated to local condition; (5) Lack of market information that consists of lack of sufficient market information and poor connectivity; (6) Lack of credit which consists of lack of access to long term credit, lack freedom of choice, and undeveloped capital market.…”
Section: Smes and Innovation Challengesmentioning
confidence: 99%
See 1 more Smart Citation